EVALUATION OF THE SEVERITY AND MONITORING THE PROGRESS OF TREATMENT OF IDIOPATHIC CONGENITAL TALIPES EQUINOVARUS BY PONSETI METHOD - Ma Nwet; Vignesh R; Theingi MM; Soe San; Ooi PC (Asian Journal of Medicine & Health Sciences, 2019)
Introduction: Congenital talipes equinovarus (CTEV), commonly known as the ‘club foot’ is a developmental disorder of the lower limb that is related with socioeconomic difficulties. Ponseti method is considered as the most popular and successful method of treatment for CTEV children. This study was aimed to evaluate the severity and monitoring the progress of initial treatment of CTEV children. Materials and methods: Forty two patients with 58 idiopathic CTEV feet treated at a hospital outpatient clinic from January 2017 to February 2018 were included in the study. Ponseti method and Pirani score system were used and the results were calculated after wearing brace for three months duration at the end of serial casting. Results: The patients in the study were in the age range of 14 days to 12 months. The mean number of changing of casting was 7.2 times. Casts were changed 1.9 times more in the severe cases than mild cases. Thirty six (85.7%) cases needed percutaneous tenotomy. There was no need to perform tenotomy for the mild cases. The initial achievement rate was 90.5 % and there were 9.5 % relapsed cases because of incorrect wearing of the brace. Statistically significant score differences were seen before and after treatment (P-value <0.000). Conclusion: Ponseti method of treatment was not free from complications but there were no major problems. Ponseti method was observed to be useful and had good outcome in the treatment for CTEV children.